Quality Analysis of Management Trainee Program Teachers for Competitive Advantage at Itikad Academy - Sawitri; K.P. Suharyono S. Hadiningrat; Verry Albert Jekson Mardame Silalahi (PT. Pustaka Cendekia Publisher, 2025)
The Management Trainee Program at Itikad Academy is a step to achieve a competitive advantage in the insurance industry. The background of this research underscores the importance of developing competent human resources in facing the challenges of the ever-evolving insurance market. This study evaluates the extent to which the teaching staff meets the competency standards required by the industry and whether the quality of teaching can be a competitive advantage for Itikad Academy. The results of the study showed that the training programs were successfully organized to provide high-quality teaching, with the teachers being mostly active practitioners in the insurance industry. Evaluations from participants showed good pedagogical and professional averages, although some teachers still needed improvement in pedagogical skills. The discussion emphasized the need for continuous development for teachers and curriculum adjustments to remain relevant to industry needs. The conclusion of this study is that even though Itikad Academy has qualified teaching staff, there is still room for improvement in order to achieve a more significant competitive advantage. Therefore, it is recommended that management conduct additional training for teachers and update the curriculum regularly. With these measures, Itikad Academy can maintain and increase its competitiveness in the insurance training institution market.